2015
DOI: 10.1021/ab500050m
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Self-Assembled Films for Rapid Hemostat and Sustained Anti-infective Delivery

Abstract: Uncontrolled bleeding and infection are the major causes of death and morbidity from traumatic wounds during military conflicts, disasters, and accidents. Because immediate treatment is critical to survival, it is desirable to have a lightweight and rapidly applicable bandageone capable of delivering a hemostat that can quickly resolve bleeding while addressing infection over short and longer time frames. It is challenging to design thin film coatings capable of multidrug release, particularly when the drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…The virulence factors produced by clinically relevant pathogenic bacteria degrade the corresponding wall material and thereby cause a release of reporter dyes that signal the infection, and/or of antimicrobials. Related multilayer approaches afford bandages capable of delivering a hemostat for quickly resolving bleeding, while sustaining an antibiotic elution for long time . An alternative approach introduced by Tram et al comprises a portable colorimetric sensor based on a bacteria‐specific RNA‐cleaving DNAzyme probe, which is translated to an easy‐to‐monitor change in pH.…”
Section: Methodsmentioning
confidence: 99%
“…The virulence factors produced by clinically relevant pathogenic bacteria degrade the corresponding wall material and thereby cause a release of reporter dyes that signal the infection, and/or of antimicrobials. Related multilayer approaches afford bandages capable of delivering a hemostat for quickly resolving bleeding, while sustaining an antibiotic elution for long time . An alternative approach introduced by Tram et al comprises a portable colorimetric sensor based on a bacteria‐specific RNA‐cleaving DNAzyme probe, which is translated to an easy‐to‐monitor change in pH.…”
Section: Methodsmentioning
confidence: 99%
“…19 Similarly, Hsu et al showed that self-assembling peptides, especially RADA16-I, are highly effective in generating in hemostasis with a hemostasis time of <10 s. 20 In their study, an antibiotic released self-assembled film developed for rapid hemostat. 21 Recently, self-assembling peptide scaffolds have been under extensive investigations for effective hemorrhage control. In spite of the shortened hemostasis time, peptides have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more research is required to determine if hm‐C provides the needed improvements in hemostatic wound care. One recent approach to infection control involves a layer‐by‐layer assembled polymeric scaffold with controlled thrombin (to promote clotting) and vancomycin (to prevent infection) release . While these scaffolds show blood clotting and antimicrobial efficacy, their film geometry prevents delivery to irregularly‐shaped wounds, and the use of vancomycin limits efficacy against modified drug‐resistant organisms.…”
Section: Introductionmentioning
confidence: 99%